Effects of scFOS on the composition of fecal microbiota and anxiety in patients with irritable bowel syndrome: a randomized, double blind, placebo controlled study. Issue 2 (31st July 2016) - Azpiroz, F.; Dubray, C.; Bernalier‐Donadille, A.; Cardot, J.‐M.; Accarino, A.; Serra, J.; Wagner, A.; Respondek, F.; Dapoigny, M.
Abstract: Background: Short‐chain fructooligosaccharides (scFOS) have beneficial effects in subjects with minor digestive complaints, but the potential mechanisms involved have not been elucidated. The aim of the study was to evaluate changes in rectal sensitivity related to the clinical effects of scFOS in a selected group of patients with irritable bowel syndrome (IBS) and rectal hypersensitivity. Methods: In 79 IBS patients (defined by Rome III criteria) with rectal hypersensitivity (defined as discomfort threshold ≤44 g) a parallel, placebo‐controlled, randomized, and double‐blind study was performed to assess the effects of dietary supplementation (5 g d −1 ) with scFOS vs placebo for 4 weeks on rectal sensitivity (primary outcome: tolerance to increasing wall tension applied by a tensostat), clinical outcomes (IBS, anxiety/depression and quality of life scores) and composition of fecal microbiota. Key Results: Rectal discomfort threshold, and IBS and quality of life scores, significantly improved during treatment, but in a similar manner in both scFOS and placebo groups; a post‐hoc analysis showed that the effect of scFOS on rectal sensitivity was more pronounced in constipation‐predominant‐IBS patients ( P =.051 vs placebo). Contrary with placebo, scFOS significantly reduced anxiety scores and increased fecal Bifidobacteria ( P <.05 for both) without modifying other bacterial groups. Conclusions & Interfences: The effect of scFOS on anxiety may be related to modulation of the gut microbiota; demonstration of effects of scFOS on rectal sensitivity may require higher doses and may depend on the IBS subgroup. Abstract : Our aim was to evaluate the effects of short‐chain fructooligosaccharides (scFOS) on rectal sensitivity, fecal microbiota, and symptoms in patients with irritable bowel syndrome. Rectal sensitivity improved with scFOS and placebo alike; however, scFOS, but not placebo, significantly increased fecal Bifidobacteria and reduced anxiety score.